Extremization of multi-objective stochastic fractional programming problem: An application to assembled printed circuit board problem - Charles, V.; Dutta, D. (Annals of operations research, 2006)
This paper addresses classes of assembled printed circuit boards, which faces certain kinds of errors during its process of manufacturing. Occurrence of errors may lead the manufacturer to be in loss. The encountered problem has two objective functions, one is fractional and the other is a non-linear objective. The manufacturers are confined to maximize the fractional objective and to minimize the non-linear objective subject to stochastic and non-stochastic environment. This problem is decomposed into two problems. A solution approach to this model has been developed in this paper. Results of some test problems are provided. [PUBLICATION ABSTRACT]